Pengaruh Metode Pembelajaran Daring terhadap Prestasi Belajar Bahasa Inggris pada Siswa Kelas XI di SMKN 1 Bogor - Wahyu Utama (NUCLEUS, 2022)
The purpose of the study was to determine how much influence online learning methods have on learning achievement in English in class XI students at SMKN 1 Bogor. The research method used in this study is a quantitative method with a descriptive approach to see how much influence the independent variable online learning method (X) has on the dependent variable of English learning achievement (Y). Furthermore, the analytical techniques used are correlation coefficient analysis, determination coefficient analysis, and simple linear regression analysis. The results of this study indicate that the value of the correlation coefficient r is -0.3178, which means that there is an influence between online learning methods on English learning achievement in class XI students at SMKN 1 Bogor. The coefficient of determination obtained a value of 10%, which means that the independent variable online learning method (X) contributes 10% to English learning achievement, while the remaining 90% is influenced by other variables not included in this study. The simple linear equation in this study is Y = 96,889 - 0.137 X. After that, the research was carried out by testing the hypothesis using a partial t test which obtained the value of tcount = 2.743 and ttable at df 67 (69-2) with a significant level of 0.05 two-way equal to 1,996 then tcount > ttable (2,743 > 1,996). With this hypothesis test, it can be concluded that there is an influence between online learning methods on English learning achievement in class XI students at SMKN 1 Bogor